Literature Review The Effect of Structured Kegel Exercises on Levator Ani Muscle Tone - Laysa Kasminata; Munawar Adhar Lubis; Edy Fakhrizal (Fakultas Kedokteran Universitas Riau, 2026)
The levator ani muscle plays a crucial role in maintaining pelvic organ support and continence. Structured Kegel exercises, or pelvic floor muscle training (PFMT), have been widely recommended to improve pelvic floor strength, but their specific effect on levator ani muscle tone remains underexplored. To evaluate the impact of structured Kegel exercise programs on the tone of the levator ani muscle based on recent literature. A literature review was conducted using 15 peer-reviewed articles published between 2014 and 2024. Studies included randomized controlled trials, clinical trials, and scoping reviews that examined structured PFMT and its effect on levator ani tone using various assessment tools, such as perineometry, ultrasonography, and electromyography. The majority of studies demonstrated a significant improvement in levator ani muscle tone following structured and supervised Kegel exercise regimens. Supervision, adherence, and exercise technique were critical to achieving optimal outcomes. Imaging and functional assessment tools consistently reported enhanced tone and pelvic floor support after intervention. Structured Kegel exercises are effective in improving levator ani muscle tone and should be incorporated into clinical protocols for preventing and managing pelvic floor dysfunctions. Further research is needed to assess long-term outcomes and standardize evaluation methods.